Pembelajaran Pembuatan Aplikasi Android Menggunakan Android Studio di Ekskul IoT SMK Wira Buana 2 - Andi Asmar Musa; Deny Priyantoko; Fian Kurniawan; Julieta Cahya Mestika; Marcellino Jonathan Bulegalangi; Matheos Oktavio Selan; Rifki Tamami; Rifqi Surya Bernada; Wahyu Muhammad Sidik; Iwan Giri Waluyo, S.Kom., M.Kom; Arief Febrian (CV. Multi Kreasi Media, 2022)
Technological advances, especially in smartphones that are increasingly developing, have a positive impact on humans in carrying out daily activities such as drawing, communicating, transacting online, studying and even doing office work. Our method is a practical method, which is an effort to give students the opportunity to experience firsthand. The students were given material on Android and Android Studio. The material presented is what is android, what is Android Studio, how it looks, how to use it and how to make an android application.